Efficiency and equity of European education and training policies - Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper reviews empirical evidence, especially from Europe, on how education and training policies can be designed to advance both efficiency and equity. Returns to educational investments tend to decrease over the life cycle. Moreover, they seem to be highest for children from disadvantaged families at early stages and for the well-off at late stages of the life cycle. This creates complementarities between efficiency and equity at early stages and trade-offs at late stages. The paper goes on to discuss specific policies for efficiency and equity at each educational stage, ranging from early childhood education and schools over vocational and higher education to training and lifelong learning. The available evidence suggests that both efficiency and equity can be enhanced by output-oriented reforms properly designed to each stage, where the state generally sets a regulatory framework that ensures accountability and funding and uses the forces of choice and competition to deliver best results. Designed this way, education and training systems can advance efficiency and equity at the same time.
Keywords: I28; H52; D6; J24; 330